Empowering First-Time Voters: SMA Negeri 1 Pabuaran’s Role in the 2024 Regional Elections - Furqon, Eki; Dewi, Lia Riesta; Firdaus, Firdaus; Suriyanti, Lili; Polem, Azmi; Oktavianus, Afriman; Mirdedi, Mirdedi; Luthfi, Muhamad Uut; Muin, Fatkhul; Gunawan, Muhammad Safaat (Probono and Community Service Journal, 2024)
The 2024 Simultaneous Regional Elections mark a critical moment in Indonesia’s democracy, especially for first-time voters who play a key role in shaping local political dynamics. This research explores the role of first-time voters in Serang Regency, Banten, focusing on their political rights and responsibilities, and the implementation of legal norms around political participation. Employing a normative research method, the study analyzes regulations and official data to assess how well first-time voters understand and exercise their political rights. The findings indicate that their participation not only enriches local political dynamics but also provides valuable insights for developing political education strategies, particularly in schools like SMAN 1 Pabuaran. Policy implications include strengthening collaboration between local governments, election organizers, and educational institutions to enhance first-time voter participation, fostering a more inclusive and transparent democratic process.